REPORTABLE DISEASE CASE AND CLOSE CONTACT INVESTIGATIONS IN THE FACE OF A PANDEMIC - Petro, Erin Mae Stanford (My University, 2021)
The Jackson County Health Department, headquartered in Independence, MO, is a multi-departmental organization that provides public health services to a population of approximately 380,000 Eastern Jackson County residents. As the Coronavirus Disease 2019 (COVID-19) pandemic became a reality in the Kansas City Metro area, the Jackson County Health Department shifted to the Incident Command Structure and sought to expand disease investigation, contact tracing, and disease containment. It was at this time that I started my Applied Practice Experience (APE) as an Epidemiology Specialist. Throughout the next nine months, I sought to learn the process of disease reporting, investigation, contact tracing, and containment at a county level, practice risk communication with both internal and external stakeholders, and apply the principles of epidemiology in specific disease scenarios. This experience, uniquely situated in the initial and sustainment phases of a novel virus pandemic, allowed me to apply didactic learning principles in a real-world atmosphere.
Keywords: Covid-19; health department; disease investigation; contact tracing; risk communication